Hodgkin’s lymphoma in a man with dilated cardiomyopathy and paraneoplastic ataxia: a therapeutical challenge - Elisabetta Abruzzese; Malgorzata Monika Trawinska; Achille Gaspardone; Antonino Morocutti; Paolo de Fabritiis (Hematology Reports, 2017)
Hodgkin’s lymphoma is a cancer of the lymphatic system. We report the case of a man with Hodgkin’s lymphoma and cardiomyopathy, for which the dilemma was whether to use the standard protocol − putting the patient at risk of worsening of heart failure, but giving him a good chance of full recovery − or not. The standard protocol was given and the patient made a full recovery without cardiac complications.